Quality of Service Provisioning in LTE-EPON Integrated Networks - Astudillo, Carlos A.; da Fonseca, Nelson L. S.; Borin, Juliana Freitag (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2016)
Passive optical networking (PON) has been recognized as a solution for backhauling next generation cellular networks. In this new scenario, QoS provisioning is an important challenge. This article proposes a Quality of Service (QoS) provisioning framework for LTE with EPON-based backhauling, which improves performance by taking advantage of information available from the backhaul as well as from the radio interface. It also introduces a QoS-aware LTE scheduler that dynamically adjusts users’ priorities to increase the overall throughput. Experimental results show how the proposals can improve resource utilization and quality of service provisioning.